Forecasting and Decision Making in the Context of COVID - Kuzomin, O.; Abu-Jassar Amer Tahseen; Lyashenko V. (IJAISR, 2023)
The results of a literature review on the topic forecasting and decision making in the context of COVID are presented. The aim of the paper is to analyze the statements and research results of various experts on COVID modeling and the implementation of a systems approach concept for the selection of a combination of models, hardware and software. Modification of modeling, prediction methods to control the emergence, development and elimination of the consequences of the "so-called pandemic" COVID. For the problem at hand a comprehensive solution of the COVID monitoring problem can be proposed which has a combination of different modeling techniques. We also provide specific data from the analysis based on wavelet coherence. These results are presented in the form of charts that help to understand some predictive estimates, be useful for future research , and confirm some data.
Keywords: COVID-19; memory -based reasoning